New sights of immunometabolism and agent progress in colitis associated colorectal cancer - Zhang, Jingyue; Chen, Chaoyue; Yan, Wei; Fu, Yu (Frontiers in Pharmacology, 2024)
Colitis associated colorectal cancer is a disease with a high incidence and complex course that develops from chronic inflammation and deteriorates after various immune responses and inflammation-induced attacks. Colitis associated colorectal cancer has the characteristics of both immune diseases and cancer, and the similarity of treatment models contributes to the similar treatment dilemma. Immunometabolism contributes to the basis of life and is the core of many immune diseases. Manipulating metabolic signal transduction can be an effective way to control the immune process, which is expected to become a new target for colitis associated colorectal cancer therapy. Immune cells participate in the whole process of colitis associated colorectal cancer development by transforming their functional condition via changing their metabolic ways, such as glucose, lipid, and amino acid metabolism. The same immune and metabolic processes may play different roles in inflammation, dysplasia, and carcinoma, so anti-inflammation agents, immunomodulators, and agents targeting special metabolism should be used in combination to prevent and inhibit the development of colitis associated colorectal cancer.